ANALISIS FEE AUDIT DAN ROTASI AUDIT TERHADAP KUALITAS AUDIT PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Srina, Srina; Purba, Mortigor Afrizal (SCIENTIA JOURNAL, 2021)
This study aims to provide empircal evidence on the efect of audit fee and audit rotation on audit quality. The population of this study are all rnanufacturing cornpanies listed on the Indonesia annual report for the 2016-2020 period. The rnethod of detemining the sarnple using purposive sarnpling method so as to obtain a sample of 35 manufacturing companies. The data collection rnethod used non-partcipant observation rnethod by downloading data from the oficial website of the Indonesian annual report. Data analsis used logistic regresion technique with IBM SPSS 25 application. The results of hypothesis testing were audit fees had a positive efect on audit quality, while audit rotation had no effect on audit quality.